The effect of fibrin glue in preventing staple-line leak after sleeve gastrectomy. An experimental study in rats - Ozdenkaya,Yasar (2019)
Abstract Purpose To evaluate the effect of fibrin glue on staple-line leak after sleeve gastrectomy. Methods Fourteen adult wistar rats 300 gr were randomized into two groups: Control group (n=7) and study group (n=7). All the rats underwent sleeve gastrectomy using lineer stapler. In the study group, fibrin glue was used to reinforce the staple-line. The rats were sacrificed 7 days after surgery. The stomach was resected, submerged in saline and exposed to excess pressure to obtain a burst pressure value. The gastric staple line was evaluated histopathologically according to the Ehrlich Hunt scale. The results of the two groups were compared. Results The mean Ehrlich-Hunt scores for inflammation, fibroblastic activity and neo-angiogenesis were similar between the groups (p>0.05). Collagen deposition was significantly higher in study group (3.42±0.53) when compared with control group (2.57±0.78) (p=0.035). The mean burst pressure was 137.8±8.5 mmHg for control group and 135.0±8.1 mmHg for study group (p=0.536). Conclusion Reinforcement of the staple-line with fibrin glue has no effect on the burst pressure after sleeve gastrectomy. More studies are needed to evaluate the precautions against leak after sleeve gastrectomy.